Lesion size and long-term cognitive outcome after pediatric stroke: A comparison between two techniques to assess lesion size. (January 2023) - Everts, Regula; Bertato, Shana; Steinlin, Maja; Slavova, Nedelina; Grunt, Sebastian; Steiner, Leonie
Abstract: Background: There is little consensus on how lesion size impacts long-term cognitive outcome after pediatric arterial ischemic stroke (AIS). This study, therefore, compared two techniques to assessed lesion size in the chronic phase after AIS and determined their measurement agreement in relation to cognitive functions in patients after pediatric stroke. Methods: Twenty-five patients after pediatric AIS were examined in the chronic phase (>2 years after stroke) in respect to intelligence, memory, executive functions, visuo-motor functions, motor abilities, and disease-specific outcome. Lesion size was measured using the ABC/2 formula and segmentation technique (3D Slicer). Correlation analysis determined the association between volumetry techniques and outcome measures in respect to long-term cognitive outcome. Results: The measurements from the ABC/2 and segmentation technique were strongly correlated (r = 0.878, p < .001) and displayed agreement in particular for small lesions. Lesion size from both techniques was significantly correlated with disease-specific outcome (p < .001) and processing speed (p < .005) after controlling for age at stroke and multiple comparison. Conclusion: The two techniques showed convergent validity and were both significantly correlated with long-term outcome after pediatric AIS. Compared to the time-consuming segmentation technique, ABC/2 facilitates clinical and research work as it requires relatively little time and is easy to apply. Highlights: Lesion size was measured using two techniques in 25 patients after pediatric stroke. The two techniques showed convergent validity. Lesion size from both techniques was significantly correlated with outcome.